Antidiabetic, Antihyperlipidemic, Antioxidant, Anti-inflammatory Activities of Ethanolic Seed Extract of Annona reticulata L. in Streptozotocin Induced Diabetic Rats - Wen, Wenbin; Lin, Yukiat; Ti, Zhenyu (Frontiers in Endocrinology, 2019)
Purpose: The present research was carried out to evaluate the possible protective effects of Annona reticulata L. (A. reticulata) ethanolic seed extract on experimentally induced-type 2 diabetes rat model. Methods:Male Albino Wistar rats were randomly divided into five groups with six animals in each group viz., control rats in group I, diabetic rats in group II, diabetic rats with 50 and 100 mg/kg/bw of ethanolic seed extract of A. reticulata in groups III and IV, respectively and diabetic rats with metformin in group V. Treatment was given for 42 consecutive days through oral route by oro-gastric gavage. Results: Administration of A. reticulata seed extract to diabetes rats significantly restored the alterations in the levels of body weight, food and water intake, fasting blood glucose (FBG), insulin levels, insulin sensitivity, HbA1c, HOMA-IR, islet area and insulin positive cells. Furthermore, A. reticulata significantly decreased the levels of triglycerides, cholesterol, LDL and significantly increased the HDL in diabetic rats. A. reticulata effectively ameliorated the enzymatic (ALT, AST, ALP, GGT) and modification of histopathological changes in diabetic rats. The serum levels of the BUN, creatinine levels, uric acid, urine volume and urinary protein were significantly declined with a significant elevation in CCr in diabetic rats treated with A. reticulata. MDA and NO levels were significantly reduced with an enhancement in SOD, CAT and GPx antioxidant enzyme activities in kidney, liver and pancreas of diabetic rats treated with A. reticulata. Diabetic rats treated with A. reticulata have shown up-regulation in mRNA expression levels of nuclear factor erythroid 2-related factor 2 (Nrf2), NAD(P)H:quinone oxidoreductase 1 (NQO1), Heme oxygenase-1 (HO-1) and protein expression level of Nrf2 with diminution in Keap1 mRNA expression level in pancreas, kidney and liver. Conclusion: From the outcome of the current results, it can be inferred that seed extract of A. reticulata exhibits protective effect in diabetic rats through its anti-diabetic, anti-hyperlipidemic, antioxidant and anti-inflammatory effects and could be considered as a promising treatment therapy in the treatment of diabetes mellitus.